Validity of research-based e-module on conservation theme to environmental literacy attitude of junior high school students - Annisa Qurotul Aini; Suroso Mukti Leksono; Septi Kurniasih (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
Ujung Kulon National Park is a national park with a lot of biodiversity that is almost extinct, but it has still not been realized by many students. Students' understanding and concern for the flora and fauna found in the TNUK area can be trained through learning based on environmental literacy. This study aims to determine the validity level of research-based e-modules on conservation themes to train environmental literacy attitudes of junior high school students. The research method used is research and development Research and Development R & D) concerning Thiagarajan, then adapted to the capabilities and needs of researchers, it is limited to 3 stages: define, design, and develop. The instrument used is a validation instrument sheet, which three validators will carry out, each on material expert validation, media expert validation, and teaching materials expert. The validation results obtained on the material expert get a percentage value of 82.88% with the category "very valid", on the media expert get a percentage value of 90.91% with the category "very valid", and on the teaching materials expert get a percentage value of 91.55% with the category "very valid" so that from the results of the validation of the research-based e-module conservation theme can be used with some revisions.Abstrak. Taman Nasional Ujung Kulon merupakan salah satu taman nasional yang mempunyai banyak biodiversitas yang hampir punah akan tetapi hal tersebut masih belum disadari oleh banyak siswa. Padahal pemahaman dan kepedulian siswa terhadap flora dan fauna yang terdapat di kawasan TNUK bisa di latih melalui pembelajaran yang berbasis literasi lingkungan.  Penelitian ini bertujuan untuk mengetahui tingkat validitas e-modul berbasis riset tema konservasi untuk melatih sikap literasi lingkungan siswa SMP. Metode penelitian yang digunakan merupakan penelitian dan pengembangan Research and Development R & D) dengan mengacu pada Thiagarajan, kemudian disesuaikan dengan kemampuan dan kebutuhan peneliti sehingga dibatasi pada 3 tahapan saja, yaitu: tahap define, design, dan develop. Instrumen yang digunakan yaitu lembar instrumen validasi yang akan dilakukan oleh 3 validator masing-masing pada validasi ahli materi, validasi ahli media dan ahli bahan ajar. Didapatkan hasil validasi pada ahli materi mendapatkan nilai persentase 82,88% dengan katagori “sangat valid”, pada ahli media mendapatkan nilai persentase 90,91% dengan katagori “sangat valid” dan pada ahli bahan ajar mendapatkan nilai persentase 91,55% dengan katagori “sangat valid” sehingga dari hasil balidasi tersebut e-modul berbasis riset tema konservasi dapat digunakan dengan beberapa revisi.